Gaya Kepemimpinan Kiai Dalam Mengelola Perguruan Tinggi - Roy Burhanuddin (THE JOER: Journal Of Education Research, 2023)
This study aims to analyze the leadership style of the kiai in managing tertiary institutions, as well as to analyze the governance of tertiary institutions on the UNU Sunan Giri Bojonegoro campus. UNU Sunan Giri is one of the private campuses under the auspices of PBNU. On January 28 2021 KH. Jauharul Ma'arif, M.Pd.I officially became Chancellor of UNU Sunan Giri. In such a long journey, the UNU Sunan Giri campus requires good governance or Good University Governance (GUG), so that Jauharul Ma'arif's leadership will determine the fate of UNU Sunan Giri in the future. As a serang kiai who leads the university, of course, he has his own characteristics in managing the UNU Sunan Giri Bojonegoro college. The method in this study is a type of qualitative research using a case study approach. The location of this research is on the UNU Sunan Giri Bojonegoro campus. Data was collected through participatory observation, structured interviews and through documentation. Data analysis in this study used the Miles and Huberman models, namely data collection, data reduction, data presentation, and drawing conclusions. As for the results of this study, it can be concluded that the kiai's leadership style in managing tertiary institutions at UNU Sunan Giri Bojonegoro is confirmed to be a charismatic - autocratic and democratic style. As well as the governance of tertiary institutions at UNU Sunan Giri Bojonegoro showing the nuances of being transparent internally but lacking externally, adequate accountability, fulfilling responsibility, creating equality, and demonstrating sufficient independence